A Novel Fuzzy Based Relay Node Deployment Scheme for Multi-hop Relay Network. (2016) - Vincent, Mariya; Babu, K. Vinoth; Arthi, M.; Arulmozhivarman, P.
Abstract: In cellular communication, a multi-hop relay (MHR) network plays an important role by reducing the cost of deployment and extending the coverage area. To achieve high transmission rate and coverage, an efficient placement of relay nodes (RN) is needed in MHR network. In this paper, a suitable deployment scheme is proposed for the RNs to obtain high system performance. By using fuzzy logic, optimum deployment sites are selected for RNs, which results in better throughput and coverage. Simulation results shows that our proposed scheme gives a better throughput and coverage performance than the existing uniform clustering and joint base station and relay station placement (JBRP) scheme.